TINJAUAN YURIDIS TENTANG PENGHINAAN LAMBANG NEGARA OLEH WARGA NEGARA INDONESIA - I Ketut Windia (Fakultas Hukum Universitas Dwijendra, 2019)
ABSTRAK State symbols and symbols of the state are two terms that have the same meaning, there is no difference. The symbol of the state is one of the symbols of state sovereignty and honor, as well as the symbol of the identity of the existence of existence of nation and state. Any person who strikes, writes, draws, or damages the State Coat with the intention of tarnishing, humiliating or demeaning the honor of the State Coat shall be subject to a maximum imprisonment of five years or a fine of not more than Rp 500 million. The formulation of the problem in this research is how is the law of humiliation of the state symbol by Indonesian citizen and how is the mechanism of determination against defamation of state symbol by Indonesian citizen. This type of research is a normative legal research moving from the state symbol of Pancasila is something sacred, in the Law of the Republic of Indonesia Number 24 Year 2009 About Flag, Language, and State Symbol, And National Anthem. The flag, language, and symbol of the country, as well as the Indonesian national anthem are symbols of state sovereignty and honor, as well as symbols of the identity of existence of nation and state. This study uses an approach that examines the applicable legislation, legal theory, and can be the opinion of scholars related to the problems in this scientific paper is the result of the insult law of the state symbol by Indonesian citizens. The conclusion of this research is the effect of the insult law of the state symbol by the citizens of Indonesia is Article 154a of the Criminal Code (KUHP)